1986
DOI: 10.1002/hep.1840060125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Volume Expansion on Hemodynamics, Capillary Permeability and Renal Function in Conscious, Cirrhotic Rats

Abstract: General and splanchnic hemodynamics (radioactive microspheres), renal function, spontaneous and histamine-mediated vasopermeability and albumin distribution space were studied in conscious control and nonascitic cirrhotic rats, before and after a moderate and sustained saline infusion (3% of body weight per 30 min + repletion of urinary losses). In basal conditions, cirrhotic rats showed lower fractional sodium excretion than did control rats (0.09 +/- 0.01 vs. 0.15 +/- 0.01%, p less than 0.005). In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
0
9

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 21 publications
1
42
0
9
Order By: Relevance
“…From the mid-1980s to the early 1990s, several investigators showed that cardiac contractile reserve is diminished in different rat models of nonalcoholic cirrhosis [16][17][18][19]. Notable is the landmark study of Caramelo and colleagues [17], who infused saline into rats with carbon tetrachlorideinduced cirrhosis.…”
Section: Systolic Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the mid-1980s to the early 1990s, several investigators showed that cardiac contractile reserve is diminished in different rat models of nonalcoholic cirrhosis [16][17][18][19]. Notable is the landmark study of Caramelo and colleagues [17], who infused saline into rats with carbon tetrachlorideinduced cirrhosis.…”
Section: Systolic Dysfunctionmentioning
confidence: 99%
“…Notable is the landmark study of Caramelo and colleagues [17], who infused saline into rats with carbon tetrachlorideinduced cirrhosis. There was a 50% decrease in cardiac output despite a 112% increase in peripheral vascular resistance [17].…”
Section: Systolic Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, it is hard to conceive that myocardial performance is impaired in patients with cirrhosis. This concept was challenged by studies that demonstrated decreased cardiac function in cirrhotic animals (33,34). In humans, Bernardi et al (35) evaluated cardiac function in 22 nonalcoholic patients with cirrhosis and demonstrated impaired myocardial contractility both at rest and on exercise that correlated with the degree of cirrhosis.…”
Section: Cardiac Dysfunctionmentioning
confidence: 99%
“…Gerbes et al found downregulated ␤-adrenergic receptor density in lymphocytes (thought to reflect cardiac ␤-adrenoceptors) from patients with decompensated cirrhosis, 4 while in the CCl 4 -rat model of cirrhosis, Caramelo et al found that volume infusions decreased cardiac output, thus indicating ventricular failure. 5 In 1990, we documented down-regulation of ventricular ␤-adrenoceptors in rats with biliary cirrhosis. 6 Since then, a large number of studies have incontrovertibly demonstrated that both patients and animal models with nonalcoholic cirrhosis show blunted cardiac inotropic and chronotropic responses to diverse stimuli such as exercise, drugs, hemorrhage, surgery, or other stresses (reviewed [7][8][9] ).…”
mentioning
confidence: 99%